The evolution of the modern worker: attitudes to work - Bryson, Alex; Forth, John (London, 2010)
"This paper examines how employees’ experiences of, and attitudes towards, work have changed over the last quarter of a century. It assesses the extent to which any developments relate to the economic cycle and to trends in the composition of the British workforce. Many of the findings are broadly positive, particularly when compared with a picture of deterioration in the late 1980s and 1990s. The onset of a major recession in the late 2000s might have been expected to herald a fundamental shift in employees’ attitudes to paid work and their working environment. The impression at the time of writing is, instead, of a more muted reaction than was seen in the early 1990s – in keeping with the more muted impact of the current recession on the labour market as a whole. "